Multidisciplinary investigation of an ancient renal stone in a mummy from Popoli, central Italy - Ventura, Luca; Arrizza, Lorenzo; Quaresima, Raimondo; Capulli, Mattia (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2022)
The renal stone found in the natural mummy of an anonymous nobleman dating to 19th century was investigated using advanced imaging modalities and analytic investigations. By this multidisciplinary approach we were able to identify the chemical components and their distribution throughout the sample. These results allowed to understand the lifestyle habits of the subject, as well as the exact pathogenesis of his disease.